Immigrants and Demography: Marriage, Divorce, and Fertility - Alicia Adsera; Ana Ferrer (Institute for the Study of Labor (IZA), 2014)
This is a draft chapter for B. R. Chiswick and P. W. Miller (eds.) Handbook on the Economics of International Migration. It discusses some of the data and methodological challenges to estimating trends in family formation and union dissolution as well as fertility among immigrants, and examines the evidence collected from the main studies in the area. The literature on immigrant family formation is diverse but perhaps the key findings highlighted in this chapter are that outcomes depend greatly on the age at migration and on the cultural norms immigrants bring with them and their distance to those of the host country. With regard to marriage we focus on the determinants of intermarriage, the stability of these unions, and the timing of union formation. The last section of the chapter reviews, among other things, a set of mechanisms that may explain the fertility behavior of first generation immigrants; namely, selection, disruption and adaptation. The section ends with a focus on the second generation.
Keywords: J11; J12; J13; J15; 330; age at migration; immigrant intermarriage; union dissolution; immigrant fertility; fertility disruption; adaptation; second generation; culture